EFFECTIVENESS OF STRUCTURED TEACHING PROGRAMME ON PREVENTION OF IRON DEFICIENCY ANAEMIA AMONG ADOLESCENT GIRLS (International Journal of Food and Nutritional Sciences, 2022)
Introduction: Adolescent girls significantly go through internal changes and mal-nutrition may lead to ineffective or unhealthy development of their body. Structured teaching allows participants or students to learn effectively and quickly through a visual presentation of an issue. Visual mode of teaching is effective in visualisation of issues that helped learners to learn comparatively better than a traditional mode of teaching.Need of the study: High school and preliminary schools need to adopt structured teaching to aware girls with various health issues as it is effective in developing knowledge and awareness among Adolescent girls. Survey and study statistics helped in understanding iron deficiency or anaemia is more common in adolescent girls.Research method: "Quasi-experimental method was used with “one group pre-test and post-test design". Structured Questionnaires was used to know about awareness of anaemia and iron deficiency in adolescent girls. Data was collected by convenient sampling technique from the 50 adolescent girls of Hoshiarpur, between the age of 12 to 18 years who are present at the time of data collection.Results: Shows that post-test result significantly improves as compared to pre-test result after implementation of structured teaching. Around 6% of adolescent girls have inadequate knowledge and 18% have adequate knowledge issues regarding anaemia, around 76% have minimal knowledge. After completion of structured training program statistics revealed that around 70% of adolescents have adequate knowledge and around 30% of adolescents still lack of knowledge.Conclusion: Structured teaching is effective in ensuring adolescent awareness about iron insufficiency